2005
DOI: 10.1021/ja043116u
|View full text |Cite
|
Sign up to set email alerts
|

Turn and Helical Peptide Handedness Governed Exclusively by Side-Chain Chiral Centers

Abstract: We have examined the preferred 3D structure of homopeptides based on an alpha-amino acid lacking the asymmetry at the alpha-carbon but exhibiting chirality in the side chains (at the two beta-carbons). These joint stereochemical properties are remarkably unusual for an alpha-amino acid. To this end, we carried out an experimental investigation by X-ray diffraction and NMR spectrometry. The results point to a well-defined relationship between screw sense of the turn and helix structures formed and side-chain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…41,42 In addition, the analysis also allowed characterization of a novel side-chain to main-chain O i Á Á Á HÀ ÀN iþ1 -type interaction, in the latter sequence. 42 Encouraged from these results and the one reported by Toniolo and coworkers, 44 to explore further the influence of the preceding C -branched amphiphilic stereogenic center on the mainchain conformation, we describe here the crystal molecular structure of another correlated model peptide: Boc-Thr-Thr-NH 2 (1). The analysis provides unambiguous experimental evidence favoring the existence of a novel structural motif that topologically mimics a typical -turn, i.e., stabilized by a main-chain to main-chain C i ¼ ¼O Á Á Á HÀ ÀN iþ3 interaction, 29,[45][46][47][48][49][50] and the Asx-turns, i.e., stabilized by a side-chain to main-chain C i þ 1 ¼ ¼O Á Á Á HÀ ÀN iþ3 interaction.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…41,42 In addition, the analysis also allowed characterization of a novel side-chain to main-chain O i Á Á Á HÀ ÀN iþ1 -type interaction, in the latter sequence. 42 Encouraged from these results and the one reported by Toniolo and coworkers, 44 to explore further the influence of the preceding C -branched amphiphilic stereogenic center on the mainchain conformation, we describe here the crystal molecular structure of another correlated model peptide: Boc-Thr-Thr-NH 2 (1). The analysis provides unambiguous experimental evidence favoring the existence of a novel structural motif that topologically mimics a typical -turn, i.e., stabilized by a main-chain to main-chain C i ¼ ¼O Á Á Á HÀ ÀN iþ3 interaction, 29,[45][46][47][48][49][50] and the Asx-turns, i.e., stabilized by a side-chain to main-chain C i þ 1 ¼ ¼O Á Á Á HÀ ÀN iþ3 interaction.…”
Section: Introductionmentioning
confidence: 78%
“…Using two enantiomeric forms of nonproteinogenic 1-amino-c-2,t-3-diphenylcyclopropane-1-carboxylic acid, Toniolo and coworkers established the influence of C -side-chain chirality on the preferred main-chain conformation of homooligopeptides. 44 Taken together, what seems to emerge is that Thr-mediated short-range interactions possibly impart exclusive conformational restrictions, and subtle variation in the preferred rotameric distribution of the polar side chain can exert a dramatic influence on the main-chain conformation(s).…”
Section: Crystal Packingmentioning
confidence: 99%
“…It usually has a right‐handed ( P ) screw sense because of the asymmetric center of the α‐carbon of L‐α‐amino acids1. Several studies have attempted to control the helical screw sense of peptides2–10, and we have recently reported that a chiral cyclic α,α‐disubstituted α‐amino acid bearing only side‐chain chiral centers, (3 S ,4 S )‐1‐amino‐(3,4‐dimethoxy)cyclopentanecarboxylic acid [( S , S )‐Ac 5 c dOM ]11 controls the left‐handed ( M ) helical‐screw sense of its homopeptides12. Incidentally, α‐aminoisobutyric acid (Aib) is widely used as a strong helical inducer; however, it does not exhibit a helical‐screw sense bias because Aib is an achiral amino acid13–15.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results of a part of this work have been reported. [29] Results and Discussion Synthesis and characterization: The preparation and characterization of the c 3 diPhe derivatives Boc-(R,R)-c 3 diPhe-OH [23] (Boc, tert-butyloxycarbonyl), Boc-(S,S)-c 3 diPhe-OH, [23] and Boc-(R,R)-c 3 diPhe-NHiPr [29] (iPr, isopropyl) were already reported. Peptide synthesis was performed step-by-step in solution beginning from the C-terminus.…”
Section: Introductionmentioning
confidence: 99%